The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/leap.1380
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge production on predatory publishing: A systematic review

Abstract: The systematic review of the research reported in this paper was conducted within the context of efforts to understand and combat predatory publishing, a new but fast‐growing area of research. It synthesizes the trends observed in knowledge production in predatory publishing, with a particular focus on the volume and distribution over time within different journals. It also looks at the composition of the predatory publishing literature in terms of the type of study, methods, topics, field of study, and contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…, 2019; Demir, 2018; Mertkan et al. , 2021a, b; Mills and Inouye, 2021; Pyne, 2017). “[A]n instrumental ethos of measurement in the management of academic work” (Spence, 2019) and exclusive reliance on whitelists based on journal indexing and Journal Impact Factors has deleterious consequences for research cultures and the integrity of science, which underline the need to revise research evaluation policies in ways that reveal commitment to quality to discourage “questionable” publication practices (Finkel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…, 2019; Demir, 2018; Mertkan et al. , 2021a, b; Mills and Inouye, 2021; Pyne, 2017). “[A]n instrumental ethos of measurement in the management of academic work” (Spence, 2019) and exclusive reliance on whitelists based on journal indexing and Journal Impact Factors has deleterious consequences for research cultures and the integrity of science, which underline the need to revise research evaluation policies in ways that reveal commitment to quality to discourage “questionable” publication practices (Finkel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…only just beginning to understand the dangers and implications of predatory journals, with 89 percent of scholarly articles written about them having been published since 2016 (Mertkan, Aliusta, and Suphi 2021).…”
Section: Predatory Journalsmentioning
confidence: 99%
“…Given that predatory journals are focused on accepting as many publications as possible rather than screening for quality, it has become a significant avenue for health misinformation and low-quality content. As a field, we are only just beginning to understand the dangers and implications of predatory journals, with 89 percent of scholarly articles written about them having been published since 2016 (Mertkan, Aliusta, and Suphi 2021).…”
Section: Predatory Journalsmentioning
confidence: 99%
“…Studies have uncovered malicious agents who seek to profit by exploiting journals' online activity. While the existence of predatory journals is common knowledge in the academic world (Beall, 2012; Lukic et al, 2014; Mertkan et al, 2021), other, less frequent, forms of online exploitation have also been reported.…”
Section: Introductionmentioning
confidence: 99%